Functional Analyses of Bovine Foamy Virus-Encoded miRNAs Reveal the Importance of a Defined miRNA for Virus Replication and Host–Virus Interaction - Cao, Wenhu (Viruses, 2020)
In addition to regulatory or accessory proteins, some complex retroviruses gain a repertoire of micro-RNAs (miRNAs) to regulate and control virus–host interactions for efficient replication and spread. In particular, bovine and simian foamy viruses (BFV and SFV) have recently been shown to express a diverse set of RNA polymerase III-directed miRNAs, some with a unique primary miRNA double-hairpin, dumbbell-shaped structure not known in other viruses or organisms. While the mechanisms of expression and structural requirements have been studied, the functional importance of these miRNAs is still far from understood. Here, we describe the in silico identification of BFV miRNA targets and the subsequent experimental validation of bovine Ankyrin Repeat Domain 17 (ANKRD17) and Bax-interacting factor 1 (Bif1) target genes in vitro and, finally, the suppression of ANKRD17 downstream genes in the affected pathway. Deletion of the entire miRNA cassette in the non-coding part of the U3 region of the long terminal repeats attenuated replication of corresponding BFV mutants in bovine cells. This repression can be almost completely trans-complemented by the most abundant miRNA BF2-5p having the best scores for predicted and validated BFV miRNA target genes. Deletion of the miRNA cassette does not grossly affect particle release and overall particle composition.